Exchange Students' Basic Literacy Analysis - Lestari, Iing Dwi; Ratnasari, Dwi; Usman, Usman (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to describe the analysis of basic literacy abilities in students as participants in the Student Exchange Program. The method used is descriptive qualitative. The subjects in this study consisted of 70 students at a public university in Banten, Indonesia. The data collected is in the form of basic literacy tests, interviews, and photos as documentation. Then the data was quantified and analysed to obtain the results of students' basic literacy skills of 81.6% in the good category. These findings showed that the Student Exchange Program is one of the activities that can develop students' basic literacy skills.